PEMASARAN HOLISTIK UNTUK JANGKA PANJANG PERUSAHAAN - Nia Kurniah (Journal of Islamic Banking, 2023)
Holistic marketing is integrated or comprehensive marketing. The company considers that all departments within the company are the most important part in achieving company goals. The holistic marketing concept includes relationship marketing, integrated marketing, internal marketing and performance marketing. The purpose of the marketing concept is to help companies achieve their goals, namely achieving maximum profits. One of the efforts to achieve company goals, companies must pay attention to trends in marketing practices. In addition to achieving maximum profit, holistic marketing also influences the company's image. To produce a good image, the company conducts marketing by carrying out social activities such as CSR (Corporate Social Responsibility).